Glycan elongation beyond the mucin associated Tn antigen protects tumor cells from immune-mediated killing. - Caroline B Madsen; Kirstine Lavrsen; Catharina Steentoft; Malene B Vester-Christensen; Henrik Clausen; Hans H Wandall; Anders Elm Pedersen (PLoS ONE, 2013)
Membrane bound mucins are up-regulated and aberrantly glycosylated during malignant transformation in many cancer cells. This results in a negatively charged glycoprotein coat which may protect cancer cells from immune surveillance. However, only limited data have so far demonstrated the critical steps in glycan elongation that make aberrantly glycosylated mucins affect the interaction between cancer cells and cytotoxic effector cells of the immune system. Tn (GalNAc-Ser/Thr), STn (NeuAcα2-6GalNAc-Ser/Thr), T (Galβ1-3GalNAc-Ser/Thr), and ST (NeuAcα2-6Galβ1-3GalNAc-Ser/Thr) antigens are recognized as cancer associated truncated glycans, and are expressed in many adenocarcinomas, e.g. breast- and pancreatic cancer cells. To investigate the role of the cancer associated glycan truncations in immune-mediated killing we created glyco-engineered breast- and pancreatic cancer cells expressing only the shortest possible mucin-like glycans (Tn and STn). Glyco-engineering was performed by zinc finger nuclease (ZFN) knockout (KO) of the Core 1 enzyme chaperone COSMC, thereby preventing glycan elongation beyond the initial GalNAc residue in O-linked glycans. We find that COSMC KO in the breast and pancreatic cancer cell lines T47D and Capan-1 increases sensitivity to both NK cell mediated antibody-dependent cellular-cytotoxicity (ADCC) and cytotoxic T lymphocyte (CTL)-mediated killing. In addition, we investigated the association between total cell surface expression of MUC1/MUC16 and NK or CTL mediated killing, and observed an inverse correlation between MUC16/MUC1 expression and the sensitivity to ADCC and CTL-mediated killing. Together, these data suggest that up-regulation of membrane bound mucins protects cells from immune mediated killing, and that particular glycosylation steps, as demonstrated for glycan elongation beyond Tn and STn, can be important for fine tuning of the immune escape mechanisms in cancer cells.